Prostate cancer in 432 men aged <50 years in the prostate‐specific antigen era: a new outlook. (8th November 2018) - Gielchinsky, Ilan; Chang, John; Cusick, Thomas; Delprado, Warick; Nguyen, Quoc; Yuen, Carlo; Savdie, Richard; Böhm, Maret; Haynes, Anne‐Maree; Scheltema, Matthijs J.; Stricker, Phillip D.
Abstract : Objective: To evaluate the clinical presentation and treatment outcomes of prostate cancer (PCa) in 432 consecutive patients aged < 50 years in the prostate‐specific antigen (PSA) era. Methods: Retrospective analysis was performed on all patients with PCa (14 570) from the years 1994 to 2017. A total of 432 consecutive patients aged < 50 years were identified. The patients were stratified by D'Amico risk groups, and their clinical presentation and treatment outcomes were analysed. The rates of biochemical recurrence after surgery were compared with the D'Amico prediction model as well as with older propensity‐score‐matched patients. The surgical pathology results in patients undergoing active surveillance (AS) were compared with those of low‐risk patients who underwent immediate surgery. Results: A total of 44%, 42% and 13% of patients harboured low‐risk, intermediate‐risk and high‐risk PCa, respectively. Their median age was 47 years and a positive family history of PCa was reported in 39.1%. Clinical stage was T1 in 65.5% and T2 in 30.0% of patients, and 2.0% of patients had metastatic disease at presentation. Radical prostatectomy (RP) was performed in 78.4% of patients ( n = 339) and the biochemical recurrence rates were 7.8% (low‐risk), 15.3% (intermediate‐risk) and 23.3% (high‐risk) at 5 years post‐surgery. These rates were lower than expected according to the D'Amico prediction model or when compared with older matched patients. A total of 74 patients with low‐risk PCa underwent AS and only 17.6% ( n = 13) required radical treatment after a median follow‐up of 46 months. The surgical pathology results in patients undergoing ASdid not differ significantly from patients with low‐risk PCa who underwent immediate surgery (positive surgical margins [ P = 0.145], tumour volume [ P = 0.257] or seminal vesicle involvement [ P = 0.100]). Of the present cohort, only 0.4% died from PCa during a median follow‐up of 65 months. Conclusions: The clinical presentation and prognosis of young patients has changed dramatically during the PSA era. Patients nowadays present with lower‐risk disease that can be treated adequately, with reassuring biochemical recurrence rates at 5 years post‐surgery. AS appears to be safe in patients with low‐risk. PCa.